Analysis of Opportunities for Agricultural Area Surveillance by UAV and Satellite in Precision Agriculture - Atanasov Asparuh I.; Atanasov Atanas Z. (Acta Technologica Agriculturae)
The presented paper focuses on comparing the capabilities for monitoring agricultural areas sown with winter wheat using satellite data and data obtained from UAVs. The NDVI vegetation index derived from both methodologies has been compared. The results show similar trends in the index variation for both methods. Although the absolute values differ, the variation curves and the zones of index deterioration are identical. The results obtained from the satellite, with a much lower resolution than that of the drone is 3.82 cm per pixel. Satellite monitoring is easily applicable and suitable for large areas, providing information every two days. However, a drawback is that cloud cover can hinder imaging, leading to extended periods without information. The drone flies below the cloud cover but is dependent on wind speed. The obtained results can help farmers to reduce the time of direct observation of winter wheat crops by performing direct observations only on the areas with reduced index.